Predicting cisplatin tolerability in older adults with head and neck cancer – Insights for improved chemoradiation outcomes - Rühle, Alexander; Weymann, Maria; Behrens, Max; Olbrich, Johannes; Kut, Carmen; Marschner, Sebastian N.; Haderlein, Marlen; Fabian, Alexander; Senger, Carolin; Bakst, Benjamin P.; Kraft, Johannes; von der Grün, Jens; et al. (Radiotherapy and Oncology, 2025)
Purpose: Cumulative cisplatin doses of ≥ 200 mg/m2 improve survival in adults with head-and-neck squamous cell carcinoma (HNSCC) undergoing chemoradiation, but many older adults with HNSCC cannot receive this prognostically relevant dose due to toxicities. This study aims to develop predictive models to assess the likelihood of older adults with HNSCC receiving ≥ 200 mg/m2 cisplatin during chemoradiation. Methods: 366 patients from the SENIOR database, an international cohort of adults ≥ 65 years with HNSCC, received definitive chemoradiation with single-agent cisplatin and were analyzed. A Generalized Linear Model (GLM), Support Vector Machine (SVM), and Random Forest Model (RFM) were trained and compared for their performance in predicting a cumulative cisplatin dose of ≥ 200 mg/m2. Results: 195 (53 %) patients achieved a cumulative cisplatin dose of ≥ 200 mg/m2. In the GLM, laryngeal carcinoma (β = 1.37, p = 0.01), tumoral p16 positivity (β = 0.69, p = 0.04), higher hemoglobin levels (β = 0.26, p = 0.002), elevated C-reactive protein (CRP) concentration (β = 0.02, p = 0.003), and increased estimated glomerular filtration rate (eGFR) (β = 0.02, p = 0.008) were associated with a higher probability of reaching ≥ 200 mg/m2 cisplatin. Hemoglobin, CRP, eGFR, and p16 status constituted the most important features in the SVM and RFM. AUC values for the GLM, SVM, and RFM were 0.70 (95 % CI, 0.67–0.73), 0.71 (95 % CI, 0.68–0.73), and 0.73 (95 % CI, 0.71–0.75), respectively. Conclusions: We developed predictive models to support clinicians in identifying older adults with HNSCC capable of tolerating ≥ 200 mg/m2 cumulative cisplatin during chemoradiation. Once validated, these models could improve personalized treatments and enhance shared decision-making in older adults with HNSCC.
CRIS-Team Scopus Importer:2025-01-31
Keywords: Chemotherapy; Cisplatin; Elderly; Geriatric; Head-and-neck cancer; Radiotherapy